2009
DOI: 10.1089/jwh.2008.1168
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Characteristics, Adherence to Walking, and Depressive Symptoms in Midlife African American Women

Abstract: Adherence to walking as well as aspects of the environment may influence depressive symptoms in African American women. In addition to supporting active lifestyles, improving neighborhood conditions may also promote mental health among African American women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 67 publications
3
61
0
1
Order By: Relevance
“…Home-based walking is good not only for healthy women but also for breast cancer patients and pregnant women, and nursing intervention has been carried out to improve their mental health as well as alleviating discomfort. In the literature in the 2000s, surveys of walking were conducted taking account of environmental factors for improvement of women's physical and mental health [1][2][3]. Home-based walking is an exercise that does not require any expenses or special training and is doable by anyone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Home-based walking is good not only for healthy women but also for breast cancer patients and pregnant women, and nursing intervention has been carried out to improve their mental health as well as alleviating discomfort. In the literature in the 2000s, surveys of walking were conducted taking account of environmental factors for improvement of women's physical and mental health [1][2][3]. Home-based walking is an exercise that does not require any expenses or special training and is doable by anyone.…”
Section: Resultsmentioning
confidence: 99%
“…As for walking, it was revealed that the amount of exercise declines without a promenade, even though there is a park nearby [5]. In a study of African-American women, a relation between the environment and their mental health, and a relation between their adherence and mental health became clear, and improvement of the environment as an external factor was proposed [2].…”
Section: To Improve the Adherence To Home-based Walkingmentioning
confidence: 99%
“…Wilbur et al [12] reported mean income for subjects was 46,000 dollars. Song and associates [28] reported 37% of the sample had income less than 35,000 dollars.…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…Sample sizes in the twenty-five studies reviewed ranged from 30 to 61,011 participates. Ten of the studies had sample sizes that were greater than 1001 participants, three studies had 1000 to 501 people [8][9][10], five had 500 to 101 people [11][12][13][14][15] and seven studies included 100 or fewer participants [5,[16][17][18][19][20]. Forty percent of the studies had sample sizes that were 1001 or greater and fifty-two percent had 500 participants or less.…”
Section: Sample Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation